INCORPORAÇÃO DE PLANTAS DE COBERTURA NO SOLO NA REDUÇÃO DA SOBREVIVÊNCIA DE Sclerotium rolfsii - ROSA, Caike Figueredo Fernandes; SOUZA, Eli Domingos de Oliveira; SANTOS, Stephany; BLANCO, Neder Henrique Martinez; GRAICHEN, Felipe André Sganzerla (ANAIS DO ENIC, 2020)
-